Prevalence and characteristics of the Solitary Rectal Ulcer Syndrome among a Cohort of Iraqi Patients with Lower Gastrointestinal Bleeding. - Abdullah, Muntadher; Al Khalidi , Nawal; Lafta, Kamal (AL-Kindy College Medical Journal, 2024)
Background: Solitary rectal ulcer syndrome (SRUS) is a benign, uncommon rectal disorder characterized by combination of symptoms, clinical findings, and histological abnormalities. It has wide range of presentations and variable endoscopic findings. Objectives: to study the prevalence of SRUS in patients presenting with lower gastrointestinal bleeding and to further evaluate this syndrome in the affected patients. Subjects and Methods: A retro-prospective descriptive study conducted in Basrah Gastroenterology and Hepatology Hospital involved revision of 350 colonoscopic reports performed for the period from January 2022–June 2023 for patients presented with bleeding per rectum. Fifteen patients fulfilled the diagnostic criteria of SRUS were reviewed and followed up. Results: the prevalence rate was 4.28%; nine male (60%), seven female (40%), mean age (22 ±9.3) years (12-45years). Mean duration of symptoms until diagnosis (8.22 ±4) weeks (3-17) weeks, females had shorter diagnosis time compared to males (5.5±2.3) (8.2±5.3) weeks respectively. The most frequent single associated symptom with the bleeding per rectum was constipation (96.3%), 20% had multiple associated symptoms. On endoscopic examination:11 (73.4%) had ulcerated lesions,4 (26.6%) non ulcer lesions [3(20%) had polypoidal lesion,1(6.6%) had only hyperemic mucosa] Majority of rectal lesions located anteriorly 13 (86.6%). At follow up; symptoms improved in 7 (46.6%), endoscopic improvement in 8 (53.3%) and histological improvement in 11(73.4%), 2(13.3%) underwent endoscopic treatment and 3(20%) ended with surgery. Conclusions: SRUS is chronic, benign disorder related to straining or abnormal defecation. It has variable clinical presentations and variable endoscopic findings rather than solitary ulcer as the name imply with different therapeutic options are available.